Correlation between Digit Ratio and Incidence of Meningioma and its Clinical Profiles - Brilliantika, Surya Pratama; Arifin, Muhammad Thohar; Istiadi, Hermawan; Winarni, Tri Indah; Muhartomo, Hexanto (Bangladesh Journal of Medical Science, 2019)
Background: Proliferation and progression of meningioma were influenced by the balance of estrogen and testosterone. Digit Ratio (DR) was a sign of prenatal exposure to estrogen and testosterone. This study intends to find the relationship between Digit Ratio and meningioma. Aim: To determine the relationship between DR and incidence of Meningioma and its Clinical Profiles (age at the onset, sex, Body Mass Indec (BMI) and histopathology grading) Methods: Analytical observational study was used with case-control design. Case group consisted of patients clinically and histopathologically diagnosed with meningioma (n=25). Patients who were not diagnosed with primary intracranial tumors were included in the control group (n=25). Matched group were conducted. Subjects of this study were patients of RSUP dr Kariadi in the period of January 2016-August 2017. This study was conducted by collecting data consisted of DR, age, sex, BMI, and grading histopathology. Tests used in this study are Chi-Square Test, Mann-Whitney Test and Fishers exact Test. Results: Digit Ratio Mean for right, left and right-left difference were 1.0041; 1.0104 and 0.0357 while for the right and left DR cutoff value 0.993; 0.989. There is a relationship between right and left Digit Ratio and incidence of meningioma (p = 0,000) with OR (Odds Ratio) Right DR = 11.17(CI95% 2,864 – 43,464) and OR left DR = 16,00 (CI95% 4,002 – 63,975). There is a relationship between Right Digit Ratio andBMI case group (p = 0,022). There is no relationship of Digit Ratio and age at onset, gender and histopathology grading (p <0.05). Conclusion: DR is risk factor of Meningioma Bangladesh Journal of Medical Science Vol.18(2) 2019 p.347-352